Anesthesia for ASD Closure in Robotic-Assisted Cardiac Surgery: A Case Report - Rizqhan, Muhammad; Hadinata, Yudi (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2026)
Background: Minimally invasive cardiac surgery (MICS) utilizes small chest incisions without sternotomy, offering faster recovery, reduced physiological stress, shorter hospitalization, and better cosmetic results. Robotic-assisted surgery is a modern approach within MICS that provides enhanced precision. However, literature on anesthesia management in robotic-assisted atrial septal defect (ASD) closure remains limited. This case report aims to provide clinical insights and support the safe adoption of such techniques.Case: A 51-year-old male with an ASD secundum and a left-to-right (L-R) shunt measuring 22x29 mm, without comorbidities, was scheduled for general anesthesia. The patient was classified as American Society of Anesthesiologists (ASA) physical status III. Monitors applied included electrocardiogram (ECG), nasopharyngeal thermometer, arterial line, central venous pressure (CVP), EtCO₂, near-infrared spectroscopy (NIRS), and transesophageal echocardiography (TEE). The patient was placed in a supine position and intubated with a 37 Fr left-sided double-lumen endotracheal tube (DLT) at a depth of 31 cm, followed by one-lung ventilation. General anesthesia was induced using midazolam 5 mg, sufentanil 10 mcg, propofol 50 mg, and rocuronium 50 mg, maintained with 1% sevoflurane and rocuronium at 10 mg/hour. A regional block was performed using a deep serratus anterior plane block (DSAPB) with a regimen of 10 ml of 0.5% isobaric bupivacaine (50 mg), 5 ml of 10% lignocaine (500 mg), and epinephrine 1:200,000, with a total volume of 40 ml. The surgery was performed on a beating heart with right femoral artery, right femoral vein, and right jugular vein cannulation. The procedure lasted 12 hours.Discussion: Robotic-assisted cardiac surgery enhances surgical accuracy but presents unique anesthetic challenges due to patient positioning, limited access, and cardiopulmonary dynamics. Anesthesiologists must optimize monitoring and maintain close team coordination.Conclusion: Robot-assisted MICS represents a significant advancement in MICS. However, anesthesiologists must pay close attention to preoperative, intraoperative, and postoperative assessments to ensure patient safety and optimal outcomes.